Biotic Ecolexicon in the Gotilon Harvest Ceremony: An Ecolinguistic Study of HKBP Congregation - Kresna Ningsih Manik (MASI Mandiri Edukasi, 2026)
This study addresses how biotic ecolexical items are represented in the Gotilon ceremony discourse of the HKBP Pardomuan Congregation and how these linguistic elements reflect ecological meanings, cultural values, and theological perspectives toward nature. The study aims to: 1) Identify biotic ecolexical items related to living beings in the Gotilon ritual discourse, 2) Interpret their ecological significance from an ecolinguistic perspective, and 3) Explain their functions within the ceremonial and cultural context. This research employs a qualitative descriptive method grounded in Arran Stibbe’s ecolinguistic framework. Data were collected through Participant observation of the Gotilon ceremony, documentation of ritual texts, in-depth interviews with church members and community elders. Data analysis focuses on identifying, classifying, and interpreting ecolexical items within their ecological and cultural contexts. The findings reveal a diverse range of biotic ecolexical items referring to plants, animals, and agricultural products, such as rice, buffalo, chicken, banyan tree, and mango tree. These lexical items function beyond literal meanings and carry deeper ecological and symbolic significance. They represent ecological values and collective memory, reflect theological beliefs about nature as a divine gift, serve as symbols of gratitude and prosperity, act as sacrificial elements in ritual practices, and function as a bridge connecting humans, nature, and God. Overall, the Gotilon ceremonial discourse reflects an integrated ecological worldview combining spirituality, agricultural traditions, and environmental responsibility.